Discourses on the decline of theories of media and communication - Rabah Saddek (Social Empowerment Journal, 2025)
This research paper examines discourses that predict the decline of theory, particularly within media and communication studies, and the rise of a post-theoretical era. It critically explores the contexts in which these claims are made, especially in relation to digital technologies and big data. The paper argues that these discourses often hold more ideological than scientific value. It also stresses the importance of revisiting the research philosophy, conceptual frameworks, and epistemological foundations within media and communication theories, as well as the social sciences more broadly. The paper calls for the development of innovative approaches that better align with the evolving technological and media landscape.